Active and participatory pedagogical practices with the Break with Knowledge and Flavors methodology: experience report (Research, Society and Development, 2020)
Awakening the student's responsibility of learning has become one of the great challenges of today's educators, since the advancement of technological resources has provided an impetus of the ways in which to pass on certain content in the classroom. This study is an experience report carried out at the Federal University of Campina Grande, with students from the 5th semester of Nursing School in the discipline of Child and Adolescent Health. The theme aims to sensitize students and teachers, focusing on active and participatory methodology, therefore collaborating in the search for a more meaningful and collective construction of knowledge, with the objective of achieving a more inclusive education with lasting and effective results. The present experience consists of the Interval with Knowledge and Flavors, in which volunteer students built discussions about subjects directly or indirectly related to the discipline, with snacks to be consumed during the construction of the dynamics. At the end of the experience, greater dynamism among the class and improvement of the student-teacher relationship were reported, and it is possible to affirm that active and participatory methodological practice is capable of providing positive emotions, improving the focus and ability to reach a higher level of performance, in addition to serving as a powerful antidote against anxiety and stress.